Macroporous bioceramic scaffolds based on tricalcium phosphates reinforced with silica: microstructural, mechanical, and biological evaluation. Issue 2 (3rd April 2022) - Novotna, Lenka; Chlup, Zdenek; Jaros, Josef; Castkova, Klara; Drdlik, Daniel; Pospisil, Jakub; Hampl, Ales; Koutna, Irena; Cihlar, Jaroslav
ABSTRACT: The positive effect of silica on microstructural, mechanical and biological properties of calcium phosphate scaffolds was investigated in this study. Scaffolds containing 3D interconnected spherical macropores with diameters in the range of 300–770 µm were prepared by the polymer replica technique. Reinforcement was achieved by incorporating 5 to 20 wt % of colloidal silica into the initial hydroxyapatite (HA) powder. The HA was fully decomposed into alpha and beta-tricalcium phosphate, and silica was transformed into cristobalite at 1200°C. Silica reinforced scaffolds exhibited compressive strength in the range of 0.3 to 30 MPa at the total porosity of 98–40%. At a nominal porosity of 75%, the compressive strength was doubled compared to scaffolds without silica. When immersed into a cultivation medium, the formation of an apatite layer on the surfaces of scaffolds indicated their bioactivity. The supportive effect of the silicon enriched scaffolds was examined using three different types of cells (human adipose-derived stromal cells, L929, and ARPE-19 cells). The cells firmly adhered to the surfaces of composite scaffolds with no sign of induced cell death. Scaffolds were non-cytotoxic and had good biocompatibility in vitro. They are promising candidates for therapeutic applications in regenerative medicine.